Cascade-responsive nano-assembly for efficient photothermal-chemo synergistic inhibition of tumor metastasis by targeting cancer stem cells. (January 2022) - Zhu, Xianqi; Li, Lin; Tang, Jin; Yang, Chunyu; Yu, Hao; Liu, Kunpeng; Zheng, Ziyan; Gu, Xinggui; Yu, Qingsong; Xu, Fu-Jian; Gan, Zhihua
Abstract: Metastasis has been widely recognized as the most lethal threats for cancer patients. Due to their special genetic and environmental context, cancer stem cells (CSCs) which are resistant to most cytotoxic drugs and radiation, are considered as the dominant culprit for metastasis. Thus, the efficient targeting and thorough elimination of CSCs are significantly urgent for the enhancement of therapeutic efficacy. Herein, we developed a facile and smart photothermal-chemo therapeutic nano-assembly system, of which the surface was modified by a sheddable PEG shell and acid-activatable pro-penetration peptide, to surmount the physiological barriers in targeting CSCs. A highly-efficient diradical-featured croconium-based photothermal agent and a natural cytotoxic heat shock protein (HSP) inhibitor were co-loaded in redox-sensitive chitosan matrices to realize the synergistic photothermal-chemo therapy. Within solid tumors, the PEG shell that prevents the nano-assembly from mononuclear phagocytic clearance could rapidly leave to expose the positively charged chitosan, and the detached iRGD could further actuate the tumor penetration of chitosan nanoparticles, and allow the CSCs targeting by selective recognition of CD44 protein. Owing to the HSP inhibition and chemo-sensitization, both the CSCs and non-CSCs could be thoroughly eliminated by the designed nano-assembly, largely inhibiting the tumor growth and metastasis. This work provides a potential strategy for CSCs-targeting drug delivery to solve the CSCs-related metastasis. Graphical abstract: Image 1 Highlights: Cascade-responsive nano-assembly efficiently targets cancer stem cells (CSCs). Newly designed diradical-featured organic photothermal agent owns photothermal conversion efficiency up to 69%. Co-delivery of photothermal agent and HSP90 inhibitor significantly down-regulates the thermal resistance of CSCs. The nano-assembly efficiently inhibits tumor growth and CSCs-related metastasis after mild photothermal-chemo treatments.